RESEPSI CERPEN MEREKA BILANG SAYA MONYET KARYA DJENAR MAESA AYU OLEH SISWA KELAS XII MA DAN SMA - Mubarokah, Sri Lestari (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research aims to describe the difference of reception between SMA and MA 12th grader on the short story entitled Mereka Bilang Saya Monyet, to describe different horizon of expectation among studenst, and offers literary lesson planning at school in the Curiculum of 2013. This research used pragmatic approach by using questionnaire with Likert scale as data collection technique. Data were analyzed using qualitative descriptive analysis technique. Results show that: the students’ reception on the intellectual aspects able to determine each indicator accordingly, but on the emotional aspects of student interest indicators show an equally low value, while on the indicators of originality, involvement and emotion, and the ability to believe mostly able to determine and assess each aspects accordingly; and the students’ horizon of expectation on indicators of expectation on the value and on the short stories reading interest are not achieved, but the indicators of expectation on the knowledge of short story contents and assessment on the value in real life are achieved. This means the categories of students based on the implementation of religious education did not affect the reception and expectation toward literary works. This research also provides the implementation of literary learning in school. Keywords: reception, short story, horizon of expectation, literary lesson planning.